Perlindungan Hukum Perkawinan Masyarakat Suku Samin - Imamul Mujahidin (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2022)
Background. The marriage of the indigenous Samin tribe in Kudus Regency shows that there are marriages that cannot be registered in the population administration. The researcher found that not being able to register the marriages of the Samin Tribe in Kudus Regency prevented them from getting civil rights. The main cause is the religious identity on the Identity Cards written by Islam even though they are not basically Muslims.Aim. This study aims to determine the factors that influence the Samin tribe community in the practice of marriage being reluctant to register it and the village government efforts to legalize the implementation of traditional marriages of the Samin tribe community without the involvement of state officials in the form of marriage registration.Methods. This research is a qualitative field research, the data are taken systematically directly from the field. This research descriptively examines observation data, interview results, and documentation.Results. Based on the results of the study, it can be concluded that the marriage of the indigenous people of the Samin Tribe is not legal under the law because it does not involve the role of the marriage registrar. The Constitutional Court through its decision Number 97/PUU-XIV/2016 gave fresh air to the people of belief in Indonesia by including the religion Belief in God Almighty in the religion column of the ID card. Based on this decision, the indigenous people of the Samin Tribe have been able to register their marriage to be recorded with the registration officer in accordance with the beliefs of the Samin Tribe.